The Influence of Survey, Question, Read, Recite, Review Method Toward Reading Comprehension Ability Mediated by Working Memory - Nani Restati Siregar; Muhammad Ilham; Mansyur M. (Jurnal Pendidikan Indonesia, 2020)
Reading comprehension plays a vital role in students' academic achievement. This empirical study aims to determine the influence of survey, question, read, recite, and review (SQ3R) method on reading comprehension ability. The impact of mediation on semantic and phonological working memory toward reading comprehension ability after being given the SQ3R method. The empirical study was Quasi-experimental with untreated control group design with dependent pretest and posttest samples. The total participants are 57 students in elementary school. Thirty of the subjects were selected based on colored progressive matrices and reading comprehension measurement in equal. In this case, 15 students as treatment groups and 15 students as a control group. Backward digit span task was used to measure phonological working memory, sentence completion, responsibility for semantic working memory, and reading comprehension test for reading comprehension ability. Causal analysis technique by SPSS MACRO PROCESS was used to examine the hypothesis of the research. The results revealed that there was an influence SQ3R method toward reading comprehension ability. Semantic working memory and phonological working memory are mediate between SQ3R and reading comprehension, but the mediating effect of semantic working memory is more reliable than phonological working memory. This research indicated that the effectivity of the SQ3R method to improve reading comprehension was mediated by working memory capacity in Bajo’s children.